ANTIBODY POLYCLONAL PRODUCTION ON RABBIT ANTI-OVINE PREGNANCY-ASSOCIATED GLYCOPROTEIN (Rabbit anti-ovPAG) - Setiatin, E.T.; Sajuthi, D.; Purwantara, B.; Talib, C.; Fathul, F.; Adiati, U.; Praira, W. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
The aim of the study was to produce polyclonal antibody (rabbit anti-ovPAG) which could detectPAG in the urine of pregnant ewes. Twelve rabbits were immunized against ovPG DEAE-TrisHCl (DT),DEAE-NaCl 20mM (DN2), DEAE-NaCl 40mM (DN4), DEAE-NaCl 80mM (DN8), DEAE-NaCl160mM (DN16), DEAE-NaCl 320mM (DN32) and DEAE-NaCl 1M (DN1) and NaCl 0.9 % as aplacebo. The 0.5 ml of isolate (purified from ovine cotyledon) was emulsified in equal volume withcomplete and incomplete Freud’s adjuvant. The mixture of each isolate and adjuvant was injected atmutiple sites along the dorsal area of rabbits by subcutaneous route. Blood were collected from marginalear vein, starting before first injection (baseline) and every 14 days. Rabbit anti-ovPAG were measuredusing Modified ELISA Technique. By using Western Blot Technique, DN32 showed the best immuneresponse among others and also could differenciate ovPAG in the urine of pregnant ewes It could beconcluded that ovPAG DN32 is a specific source of rabbit anti-ovPAG production. Protein of ovPAG atmolecular weight 31 kDa is a pregnancy protein marker of garut sheep and could be developed as amajor protein for producing antibodi.